2019
DOI: 10.1096/fj.201902015rr
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase Mg 2+ /Mn 2+ dependent‐1A and PTEN deregulation in renal fibrosis: Novel mechanisms and co‐dependency of expression

Abstract: PPM1A and PTEN emerged as novel suppressors of chronic kidney disease (CKD).Since loss of PPM1A and PTEN in the tubulointerstitium promotes fibrogenesis, defining molecular events underlying PPM1A/PTEN deregulation is necessary to develop expression rescue as novel therapeutic strategies. Here we identify TGF-β1 as a principle repressor of PPM1A, as conditional renal tubular-specific induction of TGF-β1 in mice dramatically downregulates kidney PPM1A expression. TGF-β1 similarly attenuates PPM1A and PTEN expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Extensive or recurring sublethal epithelial trauma, usually in the context of persistent transforming growth factor-β1 (TGF-β1) pathway activation, initiates and sustains a program of maladaptive repair that facilitates the progression of AKI to CKD (Friedman et al, 2013;Emlet et al, 2015;Ferenbach and Bonventre, 2015;Venkatachalam et al, 2015;Basile et al, 2016;Takaori et al, 2016;Chang-Panesso and Humphreys, 2017;Schnaper, 2017;Chung et al, 2018;Qi and Yang, 2018;Gewin, 2019;Tang et al, 2020; Figure 2). The major source of TGF-β1, as well as other proinflammatory cytokines, in the kidney is the injured epithelium although both resident and infiltrative macrophages are also major contributors (Bonventre and Yang, 2011;Liu et al, 2018;Black et al, 2019;Zhang et al, 2020).…”
Section: Tubulointerstitial Injury: the Basicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive or recurring sublethal epithelial trauma, usually in the context of persistent transforming growth factor-β1 (TGF-β1) pathway activation, initiates and sustains a program of maladaptive repair that facilitates the progression of AKI to CKD (Friedman et al, 2013;Emlet et al, 2015;Ferenbach and Bonventre, 2015;Venkatachalam et al, 2015;Basile et al, 2016;Takaori et al, 2016;Chang-Panesso and Humphreys, 2017;Schnaper, 2017;Chung et al, 2018;Qi and Yang, 2018;Gewin, 2019;Tang et al, 2020; Figure 2). The major source of TGF-β1, as well as other proinflammatory cytokines, in the kidney is the injured epithelium although both resident and infiltrative macrophages are also major contributors (Bonventre and Yang, 2011;Liu et al, 2018;Black et al, 2019;Zhang et al, 2020).…”
Section: Tubulointerstitial Injury: the Basicsmentioning
confidence: 99%
“…The contribution of TGF-β1 to the fibrotic response, importantly, was confirmed using genetic approaches. Conditional overexpression of TGF-β1 in the tubular epithelium of Pax8-rtTA-tet-o-TGF-β1 double transgenic mice induces extensive peritubular fibrosis, focal nephron degeneration (Traykova-Brauch et al, 2008;Koesters et al, 2010) and TGF-β1-dependent loss of the SMAD phosphatase PPM1A (Tang et al, 2020). Similarly, Pax8 promoter-driven expression of a ligand-independent constitutively-active TGF-β type I receptor results in the acquisition of features typical of AKI (e.g., epithelial apoptosis, necrosis and dedifferentiation; renal inflammation) (Gentle et al, 2013).…”
Section: Tgf-β/smad Signaling Drives Fibrosis In Obstructive Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have shown that even if these factors are controlled effectively, including blood pressure, blood glucose and drug damage, the process of renal fibrosis remains difficult to prevent (6). Therefore, investigating the molecular mechanism underlying the occurrence and development of fibrosis, identifying therapeutic agents and target genes that can directly interfere with the fibrotic process has become an important topic of study in recent years (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphatase and tensin homologs deleted on chromosome 10 (PTEN)/protein kinase B(AKT) pathway has been reported in tumors as a tumor suppressor 16,17 . In addition, depletion of PTEN was characteristic of renal fibrosis and overexpression of PTEN expression attenuated tubulointerstitial fibrosis [18][19][20][21][22] , inhibited macrophage polarization from M1 to M2 23,24 and suppressed inflammation responses 25,26 . Given that PTEN has been identified as a target of miR-382 in liver generation, acute promyelocytic leukemia, and tumor angiogenesis as well as oxidative stress of the tubular epithelium [27][28][29][30] , which remains unclear in kidney fibrosis.…”
Section: Introductionmentioning
confidence: 99%